Age and sexual variation of morphometric traits in Darevskia lindholmi, Szczerbak, 1962 (Sauria, Lacertidae, Darevskia) - Peskov, V.M.; Syniavska, I.O. (Збірник праць Зоологічного музею, 2016)
Based on results obtained by investigation of morphological differentiation of individuals of different age and sex, a highly correlated variation of 33 morphometric traits has been revealed in Lindholm’s rock lizard, Darevskia lindholmi (Szczerbak, 1962). It has been proved that the increase of linear body dimensions reflects the basic (ontogenetic) trend of variation of traits during late ontogenesis of D. lindholmi. It has been shown that sexual differences of some traits in D. lindholmi are almost absent, while by the linear body dimensions (the value of the first canonical root) males are larger than females. The age-related morphological differentiation of this lizards significantly exceeds sexual differences among adult individuals.